ANALISIS PEMILIHAN KARAKTER SUPERHERO SEBAGAI LISENSI PRODUK PADA MINUMAN SUSU FRISIAN FLAG (MILKY, FRUITY, DAN MUT MUT) DALAM MENARIK MINAT BELI KONSUMEN - Aji Kresno Murti; Muhammad Sani Kurniawan (Politeknik APP Jakarta, 2017)
This research is an analysis that aimed to see the suitability between super hero character (Iron Man, Spiderman, Thor, Captain America) chosen by Frisian Flag Indonesia as a license on Milky, Fruity and Mut mut products toward information allotted in the packaging. Besides, it also explored the interest of kids to the character. It was multi method research. It involved desktop-research and survey which enabled respondents to bring out their perception. The results of this study was Iron Man considered to be a very appropriate character, reflected from the survey and comparison toward the nutrition. Thus, from this research, it is a suggestion for Frisian Flag to focus Iron Man character as one of the steps to increase sales and consumer buying interest.